2016
DOI: 10.1016/j.bpj.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

MreB-Dependent Organization of the E. coli Cytoplasmic Membrane Controls Membrane Protein Diffusion

Abstract: The functional organization of prokaryotic cell membranes, which is essential for many cellular processes, has been challenging to analyze due to the small size and nonflat geometry of bacterial cells. Here, we use single-molecule fluorescence microscopy and three-dimensional quantitative analyses in live Escherichia coli to demonstrate that its cytoplasmic membrane contains microdomains with distinct physical properties. We show that the stability of these microdomains depends on the integrity of the MreB cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 55 publications
7
94
0
Order By: Relevance
“…7). As a result, the diffusive behavior of FloA and FloT assemblies resembles the classical pattern observed in eukaryotic membranes: random diffusion of proteins over short timescales 97 with reduced diffusivity or subdiffusion over longer timescales 52,98100 . Notably, FloT diffusivity is lower than FloA on longer timescales.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…7). As a result, the diffusive behavior of FloA and FloT assemblies resembles the classical pattern observed in eukaryotic membranes: random diffusion of proteins over short timescales 97 with reduced diffusivity or subdiffusion over longer timescales 52,98100 . Notably, FloT diffusivity is lower than FloA on longer timescales.…”
Section: Discussionmentioning
confidence: 61%
“…Our work provides evidence that prokaryotes and eukaryotes share fundamental mechanisms of membrane compartmentalization, presumably to maintain efficient protein-protein interactions, assist in the oligomerization of protein complexes for the optimal organization of cellular processes and metabolism, and to help avoid unfavorable protein stoichiometries and unwanted protein interactions. The cortical and cell-wall cytoskeletal structures act as effective barriers against the diffusion of membrane microdomains in both eukaryotes and prokaryotes 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GlpT (glycerol‐3‐phosphate transporter) is the major transporter for the uptake of sn ‐glycerol 3‐phosphate in E. coli . It was reported to have 12 TMHs and to function as monomer (Huang, ), which diffuses homogenously in the IM (Oswald et al, ). It was therefore expected to show homogenous membrane localization.…”
Section: Resultsmentioning
confidence: 99%
“…24), indicating that other interactions act to reduce the effective diffusion constants; a recent study observed that diffusion of a set of membrane proteins in E. coli cells was MreB-dependent and in the range 0.026–0.21 μm 2  s −1 (ref. 25). The PBP1A MSD saturated after 0.2–0.3 s (Fig.…”
Section: Resultsmentioning
confidence: 99%